Use of ceramic industry milling and glazing waste as an active addition in cement. Issue 5 (5th December 2017) - Sánchez de Rojas, María Isabel; Frías, Moisés; Sabador, Elvira; Asensio, Eloy; Rivera, Julián; Medina, César
Abstract: The beneficial effects of pozzolans on cement manufacture have encouraged their use in that industry. Traditional natural pozzolan have become less available of late, however, due to a decline in quarrying intensity aimed at minimizing the impact on the landscape. At the same time, environmental policies pursue the reduction or elimination of spoil heaps by valorizing industrial waste and by‐products as raw materials, in keeping with the principles of the circular economy. The quest for new types of waste and by‐products with pozzolanic properties has consequently become a priority line of research. This study explored the valorization of one such by‐product, the ceramic sludge resulting from fired clay industry milling and glazing, as a component in new, more eco‐sustainable cements. The sludge was characterized physically, chemically, morphologically, and mineralogically to determine its suitability as a pozzolanic addition in cement. The findings showed that ceramic sludge consists in clustered particles ranging in size from 100 μm to 1 μm. SiO2, Al2 O3, and Fe2 O3 together comprise over 70% of the total composition, while the reactive silica content is greater than the 25% required by the existing legislation. The predominant minerals are quartz, kaolinite, and muscovite, with some zircon. A study of pozzolanic reaction kinetics in the ceramic sludge/lime system revealed that over time this waste can fix lime, generating products such as calcium aluminate hydrates and C–S–H gels. The cements made with ceramic sludge proved to be standard‐compliant in terms of water demand, setting, drying shrinkage and mechanical strength.